(untitled) (Inovasi: Jurnal Diklat Keagamaan, 2017)
Performance of teachers has not been fully supported by adequate degree of competence, therefore there needs to be a comprehensive effort to improve teacher competence. To follow up the problem mentioned i n thi s research the researcher wi ll study further through empirical study by setting title: Pattern of Competence Devel opment of Madrasah Tsanawi yah Teachers State Pagu Kediri Regency. The formulation of the problem in this study as follows: (1) How is the pattern of guidance counseling teachers Madrasah Tsanawi yah State Pagu Kedi ri through teacher competency development ? (2) How is the pattern of guiding the competence of Madrasah Tsanawiyah teachers Pagu Kabupaten Kediri through teacher recruitment ? (3) How is the pattern of guiding the competence of teachers of Madrasah Tsanawiyah Negeri Pagu Kediri through the improvement of teacher quality ? This research is done naturally or natural, as it is, in the formal situation that is not manipulated the circumstances and conditions and emphasize the depiction and exposure of natural distribution data so that in this case the researcher uses qualitative descriptive approach This research belongs to the type of qualitative research. Sources of research data i s teachers MTsN Pagu Kedi ri . Data col lection techniques used in this study is by interview techniques, observation and documentation. communication. Then the data has been collected analyzed by data reduction process, data presentation and conclusion. The pattern of guiding the competence of teachers of Madrasah Tsanawiyah Negeri Pagu Kediri is done through lesson study activities. As an activity that begins with the development of joint planning, an open learning process involving a number of observers, and reflection or discussion after the implementation of learning, lesson study. Is a potential activity in improving the quality of teacher professionalism which has an impact on improving process quality and learning outcomes and creating a process of interaction between various parties.